MODEL KEBUTUHAN PENGOPERASIAN ANGKUTAN ANTAR JEMPUT (CARPOOLING) BAGI SISWA SEKOLAH DI KOTA DENPASAR - Dewa Ayu Nyoman Sriastuti; A.A. Rai Asmani. K; A.A.Gde Sumanjaya (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
Based on previous research, it is necessary to do further research to get the linkages between various variables that influence the need for operation of this shuttle transportation, by taking the title